Online Cooperative Behavior Planning Using a Tree Search Method in the RoboCup Soccer Simulation - Akiyama, H.; Aramaki, S.; Nakashima, T. (2012 4th International Conference on Intelligent Networking and Collaborative Systems, 2012)
In this paper, we propose a tree search approach to generate and evaluate cooprative behavior online in multiagent systems. It was difficult to apply a tree search methodology to tasks that the state-action space is continuous and requires realtimeness. However, it has become possible to apply such an approach since the computational resources became more powerful today. We applied a tree search method to the Robo Cup soccer 2D simulation and analyzed its effect by evaluating the team performance.